2017
DOI: 10.1038/gim.2016.192
|View full text |Cite
|
Sign up to set email alerts
|

Participant-perceived understanding and perspectives on pharmacogenomics: the Mayo Clinic RIGHT protocol (Right Drug, Right Dose, Right Time)

Abstract: PurposeTo examine predictors of understanding preemptive CYP2D6 pharmacogenomic test results and to identify key features required to improve future educational efforts of preemptive pharmacogenomic testing.Methods1010 participants were surveyed after receiving preemptive CYP2D6 pharmacogenomic test results.ResultsEighty-six percent (n=869) of patients responded. Responders were 98% white, 55% female, 57% had four or more years of post-secondary education, and aged 58.9±5.5 years on average. Among responders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 9 publications
6
57
0
Order By: Relevance
“…One salient prior study previously explored questions about PGx result education in a similar fashion to our current study. The prior study by Olson et al 22 examined patients' knowledge and perceptions of PGx after having received a mailed letter with their individual CYP2D6 results. Unlike our study, however, only post-result disclosure knowledge/attitudes were assessed (not pre-result), and patients were not required to access results via an online portal (in the Olson et al 22 study, the primary mode of delivery of results was a paper letter).…”
Section: Pharmacogenomics Results Patient Web Portalmentioning
confidence: 99%
See 3 more Smart Citations
“…One salient prior study previously explored questions about PGx result education in a similar fashion to our current study. The prior study by Olson et al 22 examined patients' knowledge and perceptions of PGx after having received a mailed letter with their individual CYP2D6 results. Unlike our study, however, only post-result disclosure knowledge/attitudes were assessed (not pre-result), and patients were not required to access results via an online portal (in the Olson et al 22 study, the primary mode of delivery of results was a paper letter).…”
Section: Pharmacogenomics Results Patient Web Portalmentioning
confidence: 99%
“…In line with this idea, we previously showed that patient-provider communications about PGx results increased patient recall of medication changes, a finding that may have direct impacts on medication adherence. 23 Additionally, Olson et al 22 found that 91% of patients reported being "much more likely" or "somewhat likely" to take their medication as prescribed if PGx information was used to help select their medications. 22 There were some potential improvements that were learned from this assessment, which will be incorporated in the next phase of portal testing and implementation.…”
Section: Pharmacogenomics Results Patient Web Portalmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients participating in that “RIGHT” study—RIGHT drug at the RIGHT dose at the RIGHT time—now have DNA sequence information in the EHR for the 17 drug-gene pairs for which “reactive alerts” are currently firing at Mayo, but, in their case, if an alert fires, it will not inform the prescriber that a genetic test is available. 29, 30 For these patients, the alert will instantly tell the care-giver the patients gene sequence with a clinical interpretation. For example, among those original 1013 subjects, if only five “common” pharmacogenes out of the 84 sequenced were included, 99.1% of the subjects had at least one actionable variant in at least one of those five genes—with many subjects having clinically actionable variant sequences in several of the five genes.…”
Section: Pharmacogenomics: Clinical Implementationmentioning
confidence: 99%